Effect of cyclic loading and an intermediate material on microtensile bond strengths of a dual-cure resin cement to dentin resin-coated with all-in-one adhesives - Sema Belli; Betül Özçopur; Cemal Yeşilyurt; Melek Akman; Nicholas Breslin; Greg Dorsman (Elsevier, 2012)
Background/purpose: The purpose of this in vitro study was to evaluate the effects of mechanical loading and an intermediate material on microtensile bond-strengths (μTBSs) of four all-in-one adhesives and a total-etching adhesive system to dentin. Materials and methods: Dentin surfaces of sound human third molars were exposed and treated with Danville Experimental (Danville Materials), G Bond (GC), Clearfil S3 Bond (Kuraray), AdheSE One (Vivadent), and Prelude total-etch (Danville Materials). Dual-curable resin (Multicore; Vivadent) build-ups were created with and without the use of Prelude Dual/Self Cure Link (Danville Materials). Two subgroups were created (with and without mechanical-loading: 5 × 104[cycles]; 50 N at 0.2 Hz). After storage at 37°C for 1 week, the μTBS test was performed. Data were calculated (MPa) and statistically analyzed (multivariate analysis of variance and Scheffe's tests). Results: Pre-test failure was observed, and no data were obtained from groups in the absence of Prelude Dual/Self Cure Link, except for the Prelude total-etch group. Prelude total-etch provided significantly higher μTBSs to dentin than did the other adhesives (P < 0.05). Bond strengths of all tested adhesives were significantly reduced upon application of the loading regimen (P < 0.05). Clearfil S3 Bond and G Bond provided significantly higher μTBSs to dentin than AdheSE One and the experimental adhesive (P < 0.05). Conclusion: Mechanical loading significantly decreased the adhesive performance, and Prelude Dual/Self Cure Link increased it for all-in-one adhesives when used with a dual-curable resin.